Hermeneutik Kontekstual:Sebuah Konstruksi Berdasarkan Filsafat Hermeneutik Modern - Margeretha Martha Anace Apituley (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
This paper seeks to see how important pre-understanding is in a contextual hermeneutic process. Therefore, by referring to the concept of pre-understanding in modern hermeneutics, both developed by Schleiermacher, Dilthey, Heidegger, Habermas, Ricoeur and Gadamer through a literature study, the author tries to see their constructive significance for contextual hermeneutics in Indonesia. In the end, it must be recognized that as a hermeneutic creature as Heidegger said, humans are not free from pre-understanding and pre-understanding is a prerequisite for doing hermeneutics. However, this pre-understanding must be criticized too, because not everything of it is emancipatory for life or even destructive tends to live.